CODE SWITCHING BY THE TEACHER IN EFL ONLINE TEACHING AND LEARNING PROCESS AT SMAN 7 MEDAN - Johannes Jefria Gultom; Edward Naibaho (Universitas Negeri Medan, 2021)
Abstract The aims of this study are to analyze the types of code switching by the teachers in EFL online teaching and learning process and to analyze the teachers’ reasons of the use code switching. This study was conducted by using descriptive qualitative design. The sources of this data were the two EFL teachers at SMAN 7 Medan. To collect the data, the researcher used zoom video recording platform to record the EFL teaching and learning process. Then, Teachers were interviewed after the teaching and learning process. There were three ways of action to analyze the data, they were data condensation, data display and conclusion drawing/verification. After analyzing the data, the researcher found that there were three types of code switching used by the teacher while teaching, namely intra-sentential switching, inter-sentential switching and tag switching. Inter-sentential switching was dominantly used by the teachers, meanwhile tag switching was the lower frequently used by teachers. In line with that, the researcher also found that there were five reasons why the teacher switched their language in EFL teaching and learning process, namely: to translating unknown vocabulary, to manage the classroom, to explain grammar, to emphasize some points, and to give empathy and solidarity.Keywords: Code switching, EFL teacher, intra-sentential switching, inter-sentential switching, tag-switching